2013
DOI: 10.1152/ajpendo.00057.2013
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial uncoupling in skeletal muscle by UCP1 augments energy expenditure and glutathione content while mitigating ROS production

Abstract: Adjeitey CN, Mailloux RJ, deKemp RA, Harper ME. Mitochondrial uncoupling in skeletal muscle by UCP1 augments energy expenditure and glutathione content while mitigating ROS production. Am J Physiol Endocrinol Metab 305: E405-E415, 2013. First published June 11, 2013 doi:10.1152/ajpendo.00057.2013.-Enhancement of proton leaks in muscle tissue represents a potential target for obesity treatment. In this study, we examined the bioenergetic and physiological implications of increased proton leak in skeletal muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 54 publications
2
41
0
Order By: Relevance
“…Because SM of UCP1‐TG mice display increased oxidative stress (51), we examined whether the metabolic reactions of the SOG pathway could eventually converge on trans‐sulfuration pathway and GSH metabolism. A recent study reported a 7‐fold increased total GSH measured in isolated mitochondria from SM of UCP1‐TG mice (52). Here we found that total GPx activity as well as GSR protein levels were increased in SM of UCP1‐TG mice, whereas total GST activity was not altered ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Because SM of UCP1‐TG mice display increased oxidative stress (51), we examined whether the metabolic reactions of the SOG pathway could eventually converge on trans‐sulfuration pathway and GSH metabolism. A recent study reported a 7‐fold increased total GSH measured in isolated mitochondria from SM of UCP1‐TG mice (52). Here we found that total GPx activity as well as GSR protein levels were increased in SM of UCP1‐TG mice, whereas total GST activity was not altered ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Despite their dysfunctional NST, UCP1‐KO mice are cold tolerant probably due to: ( i ) persistent muscle shivering (Shabalina et al , ); ( ii ) up‐regulation of ATP‐Mg 2+ /Pi inner mitochondrial membrane solute transporter gene in skeletal muscle [which could be a candidate for shivering thermogenesis (Anunciado‐Koza et al , )]; and/or ( iii ) reduction of heat loss through adrenergic vasoconstriction (Meyer et al , ). On the other hand, ectopic UCP1 expression in skeletal muscles results in reduced adiposity and augmented EE in mice (Adjeitey et al , ). Moreover, the activity of UCP1 in muscle mitigates the production of reactive oxygen species in the mitochondria but not in BAT (Adjeitey et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, ectopic UCP1 expression in skeletal muscles results in reduced adiposity and augmented EE in mice (Adjeitey et al , ). Moreover, the activity of UCP1 in muscle mitigates the production of reactive oxygen species in the mitochondria but not in BAT (Adjeitey et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, uncoupling proteins have been linked to reduction of reactive oxygen species formation (47). Although such a role for UCP1 is more controversial than for some other uncoupling proteins, there is still evidence to suggest that UCP1 may indeed function to regulate reactive oxygen species levels (48)(49)(50). Further studies are needed to explore the role of UCP1 in regulation of reactive oxygen species level during hibernation cycles.…”
Section: Discussionmentioning
confidence: 99%